How does digital infrastructure affect residents' healthcare expenditures? Evidence from Chinese microdata - Han, Huichao; Hai, Chenxi; Wu, Tianqi; Zhou, Nianchi (Frontiers in Public Health, 2023)
The healthcare expenditure is one of household burdens in the developing countries. The main current researches focus on the analysis of financial policy effect, there is lack of understanding and assessment of the impact of digital infrastructure on this issue. In this paper we use the Broadband China policy as a quasi-natural experiment to explore the impact of digital infrastructure on the resident healthcare expenditure in China. Using the differences-in-differences (DID) model and a micro-survey data, we find digital infrastructure is beneficial to reduce Chinese healthcare expenditure burden, the resident healthcare expenditure can be saved by 18.8 percent in the cities under large-scale digital infrastructure construction. Through mechanism analysis, we find that digital infrastructure reduce resident healthcare expenditure by the channel of improving commercial insurance availability and residents' healthcare efficiency. In addition, the effects of digital infrastructure on reducing healthcare expenditure are higher for those who are middle-aged, less-educated, low-income, which indicates this wave of digital construction helps bridge the social gap between the poor and the rich. This study provides valuable evidence of the contribution on social health and well-being brought by digital society construction.